Determinators of clinical outcomes in patients with chronic arthritis and systemic connective tissue disorders: COVID-19 pandemic focus - Pušica, Irena; Pušica, Irena; Lapćević, Mirjana; Ratković, Stojanka; Manić, Marina; Arapović, Mirjana (General Practice, 2024)
Introduction. Early diagnosis and treatment improveclinical outcomes, especially in chronic arthritis (CA) andsystemic connective tissue disorders (SCTD). Thanks toclinical research from the 1990s on and innovative drugs, 55million life-years have been saved. The COVID-19 pandemicbrought on medical challenges in rheumathology.Objective. The study objective was to research earlydiagnosis, time of the introduction of innovative therapy, participationin clinical research, influence of gender, age, andcorticosteroid treatment on hospitalization rate due to COVID-19 infection in CA and SCTD patients.Method. In November 2022 we performed the crosssectionalstudy in CA and/or SCTD patients using an onlinequestionnaire. The first part of the analyzed questions referredto sociodemographic characteristics and data concerningrheumatic disease - rheumatoid arthritis (RA) and otherrheumatic diseases. The second part referred to COVID-19.Data were analyzed by descriptive statistics and Pearson’sChi-square test using SPSS 29.Results. Out of the total of 176 participants, RA waspresent in 60,8%. The time from the symptom onset to diagnosiswas longer than two years. RA was more frequentlydiagnosed in the first six months (p < 0,05 - males). The innovativetherapy was used by 59,7% of the participants. Themajority of RA patients got innovative therapy after fiveyears from disease onset, which is later than in other CAs(p < 0,05 - females). There were 23,3% of the participantswho took part in clinical research, more those with RA (p
Keywords: rheumatic and musculoskeletal diseases; late diagnosis; clinical research; corticosteroids; COVID-19; vaccination